Enhanced ERbeta immunoexpression and apoptosis in the germ cells of cimetidine-treated rats - Cerri, Estela Sasso [UNESP] (Biomed Central Ltd., 2009)
Background: Cimetidine, refereed as antiandrogenic drug, causes hormonal changes in male patients such as increased testosterone and FSH levels. In the rat testis, structural alterations in the seminiferous tubules have been related to germ cell loss and Sertoli cell death by apoptosis. Regarding the important role of Sertoli cells in the conversion of testosterone into estrogen, via aromatase, the immunoexpression of estrogen receptors-beta (ERbeta) was evaluated in the germ cells of untreated and treated rats with cimetidine. A relationship between ERbeta immunoreactivity and apoptosis was also investigated in the germ cells of damaged tubules.Methods: Immunohistochemistry for detection of ERbeta and TUNEL method were performed in testicular sections of adult male rats treated with 50 mg/Kg of cimetidine (CmG) or saline solution (CG) for 52 days.Results: In CG, a cytoplasmic immunoexpression for ERbeta was observed in spermatogonia, primary spermatocytes and spermatids. An evident ERbeta immunoreactivity was always observed in the flagellum and residual bodies of late spermatids. In CmG, the cytoplasm or cytoplasm and nuclei of germ cells of the damaged tubules by cimetidine showed enhanced ERbeta immunostaining. TUNEL-labeling was usually observed in the same germ cell types exhibiting enhanced ERbeta immunoreactivity.Conclusion: The presence of ERbeta immunolabeling in the flagellum and residual bodies of spermatids reinforces the role of estrogen in spermiogenesis. The overexpression of ERbeta in the germ cells of CmG could be related to a possible interference of cimetidine on tubular androgenization and/or on the intratubular aromatase due to Sertoli cell damage. The parallelism between ERbeta overexpression and apoptosis indicates a participation of ERbeta on germ cell death.